2020
DOI: 10.1016/j.celrep.2019.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Analysis of the CLCA1 VWA Domain Suggests Mode of TMEM16A Engagement

Abstract: Highlights d A 2.00-Å crystal structure of the CLCA1 VWA domain that potentiates TMEM16A is reported d CLCA1 VWA MIDAS is in a high-affinity configuration with a disulfide bond nearby d Crystal lattice pseudoligand contacts mimic engagement with TMEM16A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(126 reference statements)
0
10
0
Order By: Relevance
“…CLCA1 is a secreted potentiator of the calcium-activated chloride channel. Its Willebrand factor type A domain elevates TMEM16A expression and activity within minutes, suggesting a dynamic association of TMEM16A with many partners that control its expression at various levels [36,37]. Thus, CLCA1 appears to work by an entirely different mechanism, namely by stabilizing expression of TMEM16A in the plasma membrane.…”
Section: Compoundmentioning
confidence: 99%
“…CLCA1 is a secreted potentiator of the calcium-activated chloride channel. Its Willebrand factor type A domain elevates TMEM16A expression and activity within minutes, suggesting a dynamic association of TMEM16A with many partners that control its expression at various levels [36,37]. Thus, CLCA1 appears to work by an entirely different mechanism, namely by stabilizing expression of TMEM16A in the plasma membrane.…”
Section: Compoundmentioning
confidence: 99%
“…Von Willebrand factor also acts as a receptor for proteasome-mediated degradation for ubiquitin-like proteins. 26 - 28 Eukaryotic initiation factor 2B (EIF2B) is a GTP exchange factor necessary for protein synthesis. Stress responses lead to increase protein synthesis during which stress response proteins are produced, these proteins activate the kinases, which leads to phosphorylation of the eIF, and this reduces the activity of EIF2B.…”
Section: Discussionmentioning
confidence: 99%
“…105 Expression of hCLCA1 in two mammalian cell lines led to stimulation of endogenous CaCCs. [198][199][200][201] first showed that this process involved the proteolytic self-cleavage of hCLCA1 due to the presence of a novel zincin metalloprotease domain at its N-terminal end. The stimulation of CaCCs was not linked to the proteolytic activity of hCLCA1 per se because exposure to an N-terminal mutant fragment lacking enzymatic activity still led to enhanced CaCC activity.…”
Section: Clca1 Andmentioning
confidence: 99%
“…Subsequent reports demonstrated that the von Willebrand factor type A (vWF) domain located in the N-terminus of hCLCA1 is responsible for the interaction with ANO1. 201,202 The engagement of ANO1 was speculated to involve Mg 2+ -dependent binding of the extracellular loop between TMD9 and 10 of ANO1 to a conserved metal ion-dependent adhesion site (MIDAS) motif on the vWF domain of hCLCA1. Finally, the effects described above are not unique to hCLCA1 as the expression of hCLCA2 in a HEK-293T cell line stably expressing hANO1 nearly doubled the magnitude of I Cl(Ca) evoked by the Ca 2+ ionophore ionomycin.…”
Section: Clca1 Andmentioning
confidence: 99%
See 1 more Smart Citation